(untitled) (Medico Legal Update, 2020)
Background: Gingival recession considers as a common condition that associated with transposition of the margin of the gingiva in to the position apical to the cemento-enamel junction which consequently result in an exposure of the root . Inflammatory biomarker including interferon-gamma and tumor necrosis factor-alpha associated with a significant role in periodontal tissue destruction . The main goals of current study were to compare the levels of interferon-gamma and tumor necrosis factor-alpha in patients with different degree of gingival recession and control participants. Material and method: Blood samples taken from twenty four male participants and they grouped in to three groups as: group 1(8 control subjects) , group 2 (8 patients with class 1 and 2 gingival recession )and group 3 (8 patients with class 3 and 4 gingival recession). Enzyme-linked Immunosorbent Assay was utilized to evaluate tumor necrosis factor-alpha and interferon-gamma levels. Results : The levels of both biomarkers were greater in group 3 than group 1 and group 2 as well as group 2 had higher levels of these biomarkers than group 1. Conclusion: Interferon-gamma and tumor necrosis factor-alpha could reflect periodontal destruction in patients with gingival recession